(3OQGSI ebGQfIs - (3eYf YHO GdQMje YHO GdYRjR(B, (3LhjMGfs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2008)
(3jYQV gPG GdcJGH aj WjGJg (B: (3GdebOeI(B-(3GdaUd GdChd (B: (3QCS eGd TQcGJ GdCehGd GdNGUI (B: (3GdeHMK GdChd (B: (3GdJYQja HQCS eGd TQcGJ GdCehGd GdNGUI (B: (3GdeWdH GdKGfj (B: (3JbSje QCS GdeGd (B: (3GdeWdH GdQGHY (B: (3eHOC KHGJ QCS GdeGd (B: (3GdeHMK GdKGfj (B: (3fchjf QCS eGd TQcGJ GdCehGd GdNGUI (B: (3GdeWdH GdChd (B: (3YfGUQ QCS GdeGd (B: (3GdeWdH GdKGfj (B: (3JMOjO QCS GdeGd(B-(3GdaUd GdKGfj (B: (3eGgjI JNajV QCS eGd TQcGJ GdCehGd GdNGUI (B: (3GdeHMK GdChd (B: (3eaghe JNajV QCS eGd TQcGJ GdCehGd GdNGUI hJejjRg eeG jTJHg Hg (B: (3GdeWdH GdKGfj (B: (3JejjR GdJNajV eeG jTJHg Hg (B: (3GdeHMK GdKGfj (B: (3CSHGH JNajV QCS eGd TQcGJ GdCehGd GdNGUI hTQhWg (B: (3GdeWdH GdChd (B: (3CSHGH GdJNajV(B-(3GdaUd GdKGdK (B: (3WQb JNajV QCS eGd TQcGJ GdCehGd GdNGUI (B:(3GdeHMK GdChd (B: (3JNajV QCS GdeGd HJNajV GdbjeI GdGSejI ddGSge ChYOOgG (B: (3GdeHMK GdKGfj (B: (3JNajV QCS GdeGd Yf WQjb TQGA GdTQcI dGSgegG (B: (3GdeWdH GdChd (B: (3Mb GdTQcI aj TQGA GSgegG (B: (3GdeWdH GdKGfj (B: (3TQGA GdCSge HbUO JNajV QCS GdeGd (B- (3GdaUd GdQGHY (B: (3GLQGAGJ JNajV QCS eGd TQcGJ GdCehGd GdNGUI hGdWYf ajgG (B: (3GdeHMK GdChd (B: (3GLQGAGJ JNajV QCS eGd TQcGJ GdCehGd GdNGUI (B: (3GdeWdH GdChd (B: (3GdELQGAGJ GdSGHbI Ydi GJNGP bQGQGJ GdJNajV (B: (3GdeWdH GdKGfj (B: (3GUOGQ bQGQ GdJNajV (B: (3GdeHMK GdKGfj (B: (3GdWYf aj bQGQ JNajV QCS eGd TQcGJ GdCehGd GdNGUI (B: (3GdeWdH GdChd (B: (3GdCTNGU GdPjf dge Mb GdWYf aj bQGQ GdJNajV(B.s
(3HHdjhZQGajG(B: (3U(B.309s
Keywords: (3GdTQcGJ GdNGUIs; (3QCS GdeGds